Transatlantic Integration after the Cold War. Romania ‐ a Strategic Pillar within the Euro‐Atlantic Community - GHIDIU, Iulia-Anamaria (2023)
Therefore, the topic of the evolution of the transatlantic relation after the Cold War is, in fact, a very complex puzzle combining many common interests, common challenges, pros and cons, individual perceptions and also shared Western democratic values, a topic of contemporary debate that challenges even by the multiple perspectives it can be approached from.The main interrogations guiding the research focus on the following aspects:1. What are the main pillars/policies supporting/distorting a positive trend of the transatlantic relation regarding politics, ideology, trade, energy, environment, culture?2. To what extent can Romania influence the evolution of the EU-US relation in the future, as both a pro-European and pro-American country?3. What are the best-case, the most probable case and the worst-case scenarios regarding future cooperation between the EU and the US?